2011
DOI: 10.1007/s00223-011-9476-2
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Exercise has Long-Term In Vivo Protective Effects on Osteocyte Viability and Bone Strength Following Ovariectomy

Abstract: Osteocytes are recognized as having a pivotal role in bone tissue homeostasis, and stimuli that increase osteocyte death result in decreased bone tissue quality. Previous in vitro studies have shown that mechanical stimulation prevents osteocyte death; however, in vivo evidence of this protective effect is limited. The aim of this study was to investigate if mechanical stimulation provided by voluntary exercise reduces osteocyte death caused by estrogen deficiency. Thirty-two female Wistar rats (5 months old) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 44 publications
1
33
0
Order By: Relevance
“…The osteocyte density was higher (~20%) in the exercised compared with the control fish, indicating that osteoblasts are embedded in the osteoid more frequently during exercise. Similarly, a higher number of osteocytes have been identified in exercised mice [40] and rats [41]. The increased osteocyte number might result from a combination of an increased osteoid production together with an increase in the pool of osteoblasts that is available for being entrapped within the bone matrix.…”
Section: Discussionmentioning
confidence: 96%
“…The osteocyte density was higher (~20%) in the exercised compared with the control fish, indicating that osteoblasts are embedded in the osteoid more frequently during exercise. Similarly, a higher number of osteocytes have been identified in exercised mice [40] and rats [41]. The increased osteocyte number might result from a combination of an increased osteoid production together with an increase in the pool of osteoblasts that is available for being entrapped within the bone matrix.…”
Section: Discussionmentioning
confidence: 96%
“…Long duration running may be preventative against MIA-induced cartilage and/or osteocyte death. For example, voluntary exercise was shown to be protective against OVX-induced osteocyte death in rats, and enhanced muscle mass in exercised but not sedentary rats [7]. Finally, it may be possible that the longer prior running regimen simply resulted in rats that were more physically fit and thus more able to sustain the MIA chronic pain manipulation [5658].…”
Section: Discussionmentioning
confidence: 99%
“…Voluntary wheel running in rodents has been shown to enhance muscle viability and bone strength [79], attenuate allodynia and elevated IL-1β levels in a model of neuropathic pain [10], and increase protective CD206 macrophage production in a model of muscle pain, and decrease pain- and stress-related measures in a model of inflammatory pain [11,12]. Although there is an increasing literature base on exercise-pain interactions [10,11,13,14], less is known about how the behavioral mechanism of wheel running acquisition duration (i.e., prior wheel running) affects the expression of chronic pain-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study reported that voluntary running for 9 weeks improved cortical porosity in ovariectomized and sham rats (Fonseca et al. ). Regardless of exercise methods, previous study was consistent with our study.…”
Section: Discussionmentioning
confidence: 92%